2022
DOI: 10.3390/hearts3030009
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Predictors, and Outcomes of Myocardial Injury in Hospitalized COVID-19 Patients—An Observational Retrospective Study

Abstract: COVID-19 mainly causes pulmonary manifestation; nonetheless, its systemic inflammatory response involves multiple organs, including the heart. We aimed to evaluate the prevalence, predictors, and outcomes of myocardial injury in hospitalized patients with SARS-CoV-2 infection. Methods and Results: We performed an observational retrospective analysis on patients hospitalized with COVID-19 in a moderate-sized community hospital system. Myocardial injury was defined as highly sensitive troponin T levels in the 99… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The main finding, confirming this study, is that the prevalence of cardiovascular diseases is significantly increased among patients with troponin positive and that this increase can be attributable to traditional risk factors. One previous study found 56.1 % of prevalence of myocardial injury among hospitalized COVID-19 patients [5] . Further research may be needed to understand the pathophysiology of Covid-19 affecting cardiovascular diseases.…”
mentioning
confidence: 94%
“…The main finding, confirming this study, is that the prevalence of cardiovascular diseases is significantly increased among patients with troponin positive and that this increase can be attributable to traditional risk factors. One previous study found 56.1 % of prevalence of myocardial injury among hospitalized COVID-19 patients [5] . Further research may be needed to understand the pathophysiology of Covid-19 affecting cardiovascular diseases.…”
mentioning
confidence: 94%